Entre disparition et essentialisation : Le Sud des États-Unis et la migration inversée des Africains-Américains depuis les années 1970 - Nicolas RAULIN (E-REA)
This paper looks at the migration of African Americans to the South of the United States since the 1970s by focusing on the metropolitan area of Atlanta in Georgia. A first part presents the methodology used for this research that integrates quantitative and qualitative data to obtain a more nuanced understanding of the migration. A second part of this analysis is dedicated to scrutinizing how migrants’ perspectives can shed light on the great changes that have affected regional spaces in the US, and most particularly their convergence. Finally, the very category of the Southern region is tackled in a third part to understand how it still influences social representations when it comes to migration: the Southern space can be both represented as a black diasporic area and used as a category of exclusion for black newcomers in the metropolitan area of Atlanta.